An investigation into the differences between English and Arabic position and order of adjectives: A contrastive study with pedagogical implications - Amer, Walid (Beirut Scientific Research Centre in Aljinan University, 2014)
Lots of studies have been done on the position and order of adjectives in English. However, as far as my knowledge is concerned, no analytical and contrastive study has been conducted on this point in English and Arabic. Thus, this paper reviews the latest studies done on the position and order of adjectives in English and Arabic. Then, it describes the differences between the position and order of adjectives in both languages. The study also touches upon the pedagogical implications for teaching adjectives in English. Here, it is believed that the Arab learners of English encounter great difficulty in constructing sentences involving a number of adjectives. One of the most prominent causes of committing errors found in this area is assumed to be the linguistic differences between the adjective position and order in English and Arabic. To prove this assumption, the researcher applied his study on the Islamic University of Gaza (IUG) freshman students majoring in English to test their perception of the position and order of English adjectives and to shed light on the areas of difficulty that students encounter when using English adjectives. The paper focuses on the errors most students commit concerning the position and order of English adjectives and ends with recording some recommendations for solving this pedagogical problem.
(3GdfhY (B: Articles
Keywords: Enseignement des langues; Teaching languages; (3JYdje GddZGJs